Elucidation of Layer Ducks Business Prospects In KWT (Farming Women Group) Purbolinggo Districts Lampung Timur - Eny Ivan's Eny; Novita; Wintari Mandala (INTASTAWIT Journal (Indonesian Tasamuh, Tawassuth, I'tidal, dan Tawazun), 2021)
In increase household economy, participation of housewife was very signifficant to be empowered through institution media that is Group of Farming Woman (Kelompok Wanita Tani (KWT)). Government have been support the existence of KWT with cattle donation like layer duck cultivation that managed in groups. But, layer duck cultivation in KWT Tambah Luhur Village, Purbolinggo didn`t optimal. Through community dedication activity, community should be motivated and people thought that housewive played an important role in family welafare, moreover in increase national food security. Based on above, this activity aim to motivate and train KWT in optimalize role of KWT especially in develop layer duck cultivation result of governernment donation. Method used in community dedication activity pengabdian such as eludication with materials that supported development of layer duck cultivation about layer duck business prospect, technique of layer duck cultivation (home system), and variation of processing of layer duck flesh. Result and impact of this community dedication activity was motivated of KWT to develop layer duck business in groups.